Efficient Boundary Extraction from Orthogonal Pseudo-Polytopes: An Approach Based on the 𝑛D-EVM - Ricardo Pérez-Aguila (Journal of Applied Mathematics)
This work is devoted to contribute with two algorithms for performing, in an efficient way, connected components labeling and boundary extraction from orthogonal pseudo-polytopes. The proposals are specified in terms of the extreme vertices model in the 𝑛-dimensional space (𝑛D-EVM). An overview of the model is presented, considering aspects such as its fundamentals and basic algorithms. The temporal efficiency of the two proposed algorithms is sustained in empirical way and by taking into account both lower dimensional cases (2D and 3D) and higher-dimensional cases (4D and 5D).